Pengaruh Kegiatan Keagamaan Terhadap Pembentukan Sikap Spiritual Siswa Di Ma Darul Faizin Catakgayam Jombang - Dina Vadilla Ramadhani (Kampus Akademik Publiser, 2024)
Education is very important to shape humas to become perfect creatures. It is in these religious activities that student can hone and apply religious character values in a more cmplex manner. Therefore, the author is interesed in conducting this research. The aim of this research is to find out whether there is an influence of religious activities on the formation of Students’ Spiritual Attitudes at Madrasah Aliyah Darul Faizin Catakgayam Mojowarno Jombang. Based on this research, the researcher formulated the problem as follows: 1. To determine the Influence of Religious Activities at Madrasah Aliyah Darul Faizin Catakgayam Mojowarno Jombang. 2. To determine the Influence of the formation of students’ Spiritual Attitudes at Madrasah Aliyah Darul Faizin Catakgayam Mojowarno Jombang. 3. To determine the Influence of Religious Activities on Formation of Students’ Spiritual Attitudes at Darul Faizin Catakgayam Mojowarno Jombang. The approach used is a quantitative approach. Which is ex post facto, data collection is carried out using observations, questionaires and documentation. Test the validity of the instrumet using Person Product Moment correlation and test reabilitty using the Cronbach’s Alpha formula. Meanwhile, prerequisite analysise tests include normality tests, correlation tests, hypothesis tests include simple linear regression equations.Based on the research, research shows that 1. Religious activities in the baliwa year which received a minimum score of 19-22 were 4 respondents with a score of 11,1%, those who got a maximum score of 51-55 were 5 respondents with a score of 13,0%, 2. The Formation of Spiritual attidues was known that those who got a minimum score of 58-61 were 6 respondents with a score of 16,7%, those who got a maximum score of 94-97 were 2 respondents with a score of 5,6%. 3. The result of the simple regress test showed that there was an Influence between Religious Activities on the formation of Sparimal Attitudes was Madrasag Aliyah Darul Faizin Catakgayam Mojowarno Jombang, the amount is 59,9%, while the remaining 40,1% is influenced by other variables not included in this model.